Low hydrogen iron powder covered electrode

JP7638595B2Active Publication Date: 2025-03-04NIPPON STEEL WELDING & ENGINEERING CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021056217
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-29
Publication Date
2025-03-04
Estimated Expiration
2041-03-29

AI Technical Summary

Benefits of technology

【0015】 本発明を適用した鉄粉低水素系被覆アーク溶接棒によれば、780MPa級高張力鋼での直流電源を用いた多層盛溶接において、鋼材と同等以上の強度が得られ、アーク安定性等の溶接作業性が良好であり、かつ、低温での安定した靱性が得られ、作製した溶接継手において良好な曲げ性能が得られる。したがって、各種鋼構造物に対する溶接継手の信頼性を大幅に向上することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638595000001
    Figure 0007638595000001
  • Figure 0007638595000002
    Figure 0007638595000002
  • Figure 0007638595000003
    Figure 0007638595000003
Patent Text Reader

Abstract

To provide a low-hydrogen iron-powder coated arc welding rod for 780 MPa class high-strength steel, the welding rod having good welding workability and being capable of providing a weld metal with appropriate strength, bending performance, and low-temperature toughness.SOLUTION: A low-hydrogen iron-powder coated arc welding rod contains Mn: 3.0-6.0%, Ni: 3.5-7.5%, Mo: 0.3-1.3%, Cr: 0.2-1.0%, Si: 2.0-5.0%, SiO2 conversion value of Si oxides: 3.5-7.5, Ti: 0.2-1.5%, TiO2 conversion value of Ti oxides: 1.0-5.0%, metal carbonates: 25-45%, metal fluoride: 5-15%, Al2O3 conversion value: 2.0% or less, MgO conversion value: 0.8% or less, total of Na and K conversion values: 1.5-3.0%, and Fe: 20-30%, by %mass to the total mass of the coating material, and is characterized in that a relationship among the contents of the Mn, Ni, Mo, and Cr is within a predetermined range, and that the coating is performed at a coverage rate of 25 to 40%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an iron powder low-hydrogen covered metal arc welding electrode which has good arc stability, a tensile strength of 780 MPa or more, and good low-temperature toughness and bending performance of a welded joint, particularly in arc welding using a DC power source. [Background technology]

[0002] Low-hydrogen covered electrodes have good arc stability and excellent crack resistance and low-temperature toughness of the weld metal, and are therefore widely used in areas with strong restraint and for welding high-tensile steel.

[0003] On the other hand, with the recent increase in the size of welded structures, there is a demand for higher strength steel materials to be used. Also, in order to ensure safety in large marine structures and spherical tanks aimed at the development of natural resources, it is important to further improve the low-temperature toughness of the weld metal and ensure excellent mechanical performance, such as by ensuring sufficient strength. However, since the compatibility of high strength and low-temperature toughness in weld metal is generally a contradictory property, the development of a new method to achieve both high strength and low-temperature toughness is desired.

[0004] In response to this situation, several proposals have been made as means for improving the mechanical properties of weld metal. For example, Patent Document 1 discloses a technique related to a covered metal arc welding rod that aims to obtain a weld metal with excellent low-temperature toughness even when the Ni content is 1 mass% or less. However, the technique described in Patent Document 1 has a problem that when welding is performed using a DC power source, magnetic arc blow and one-sided melting of the coating are likely to occur, making it difficult to ensure sufficient welding workability.

[0005] Patent Document 2 discloses a low-hydrogen covered electrode that provides excellent arc stability and excellent weld metal strength and low-temperature toughness when multi-layer welding is performed on the circumference of a steel pipe of 490 MPa or more using a DC power source. However, the technology disclosed in Patent Document 2 is applied to multi-layer welding of the circumference of a steel pipe of 490 MPa or more, and is a technology for a welding material with a tensile strength of 550 to 650 MPa. Therefore, sufficient characteristics cannot be obtained with a welding material of 780 MPa or more.

[0006] Also, Patent Document 3 discloses a technology for a low-hydrogen covered metal arc welding rod that ensures stable mechanical performance of the weld metal when the tensile strength of the deposited metal is 590 MPa or more, good welding workability in all positions, and low-temperature toughness. However, the technology disclosed in Patent Document 3 has a problem in that the welding rod is expensive because Ni is added to the steel core wire. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2014-151338 A [Patent Document 2] JP 2016-203253 A [Patent Document 3] JP 2010-253495 A Summary of the Invention [Problem to be solved by the invention]

[0008] Low-hydrogen covered electrodes are generally designed for use in Japan with AC power sources for welding. Recently, however, there has been a demand for the development of low-hydrogen covered electrodes that can be used with DC power sources, which are cheaper power sources, for example, in on-site welding of spherical tanks and marine structures overseas.

[0009] When a low-hydrogen covered electrode is used for welding with a DC power source, magnetic blow and one-sided melting of the coating material occur, making the arc unstable and making it difficult to obtain a sound bead. For this reason, there is a need for the development of an iron powder low-hydrogen covered electrode that has excellent arc stability and good mechanical properties of the weld metal even when a DC power source is used.

[0010] The present invention has been devised in view of the above problems, and has an object to provide an iron powder, low hydrogen type covered metal arc welding electrode for 780 MPa class high tensile steel, which has good welding workability such as arc stability and produces welded joints with excellent low temperature toughness and bending workability in multi-layer welding using a DC power source on higher strength 780 MPa class high tensile steel. [Means for solving the problem]

[0011] The present invention is a method for manufacturing a steel core wire having a coating material applied thereto. For multi-layer welding of 780MPa-class high-tensile steel using a DC power source In the case of an iron powder low hydrogen type covered metal arc welding electrode, the coverage of the coating material is 30-45% by mass based on the total mass of the welding electrode, and the composition of the coating material is, by mass based on the total mass of the coating material, 3.0-6.0% Mn, 3.5-7.5% Ni, 0.3-1.3% Mo, 0.2-1.0% Cr, 2.0-5.0% Si, 3.5-7.5% total of Si oxides converted into SiO2, 0.2-1.5% Ti, 1.0-5.0% total of Ti oxides converted into TiO2, 25-45% total of one or more metal carbonates, or 25-45% total of one or more metal carbonates. The coating agent is characterized in that it contains two or more metal fluorides in total: 5 to 15%, the total of Al oxides in terms of Al2O3: 2.0% or less, the total of Mg oxides in terms of MgO: 0.8% or less, and the total of one or more of Na oxide, Na fluoride, K oxide and K fluoride: 1.5 to 3.0% in terms of Na and K, and the Mn, Ni, Mo and Cr are 150 to 300 in terms of formula (1), and further contains Fe: 20 to 30%, and the total of the remainder consisting of impurities is 1.0% or less.

[0012] 2.3 × [Mn] + 38.5 × [Ni] + 4.2 × [Mo] + 2.1 × [Cr] formula (1) Here, [ ] indicates the mass % of each component relative to the total mass of the coating agent.

[0013] The low hydrogen iron powder covered metal arc welding electrode is characterized in that the coating contains 0.5% or less of Ca oxide in terms of CaO in total mass percent relative to the total mass of the coating.

[0014] The present invention further provides an iron powder low hydrogen type covered metal arc welding electrode, characterized in that the coating material has a total mass percentage of Zr oxide calculated as ZrO2 of 1.5% or less based on the total mass of the coating material. Effect of the Invention

[0015] The low hydrogen iron powder covered metal arc welding electrode of the present invention provides strength equal to or greater than that of steel in multi-layer welding of 780 MPa class high tensile steel using a DC power source, good welding workability such as arc stability, stable toughness at low temperatures, and good bending performance of the welded joints produced. Therefore, the reliability of welded joints for various steel structures can be significantly improved. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] In order to solve the above-mentioned problems, the present inventors conducted a detailed study on an iron powder low-hydrogen covered metal arc welding electrode, in particular the component composition of the coating material thereof, which is capable of obtaining a strength equal to or greater than the above strength, good welding workability such as arc stability, stable low-temperature toughness, and good bending performance of the produced welded joint in multi-pass welding of 780 MPa class high tensile steel using a DC power source.

[0017] As a result, the following findings were obtained, and the present invention was developed by adjusting the various components according to these findings.

[0018] (1) By adjusting the contents of Mn, Ni, Mo, and Cr to appropriate amounts, it is possible to ensure the strength of the weld metal and good bending performance of the welded joint.

[0019] (2) The toughness of the weld metal at low temperatures can be improved by optimizing the content of metal carbonate, Si, and Ti and the coating rate on the steel core wire.

[0020] (3) In order to stabilize the arc and reduce the amount of spatter generated, which is related to the welding workability, the amount of Si, Ti, Ti oxide (TiO2 equivalent value), metal carbonate, metal fluoride, and one or more of sodium oxide, sodium fluoride, potassium oxide, and potassium fluoride can be adjusted to an appropriate amount.

[0021] (4) The bead shape and bead appearance can be improved by adjusting the total content of silicon oxide (SiO2 equivalent), titanium oxide (TiO2 equivalent), metal carbonates, metal fluorides, and magnesium oxide (MgO equivalent).

[0022] (5) The removability and encapsulation properties of the slag can be improved by adjusting the total amount of silicon oxide (SiO2 equivalent), metal carbonate, metal fluoride, and aluminum oxide (Al2O3 equivalent) to an appropriate amount.

[0023] (6) In order to prevent rod burn, in which the welding rod itself becomes red hot, the Fe content can be adjusted to an appropriate amount. In order to prevent one-sided melting of the welding rod protective tube, the metal fluoride and Fe contents can be adjusted to an appropriate amount. The productivity of the welding rod, such as the paintability of the coating agent, can be improved by adjusting the total amount of one or more of sodium oxide, sodium fluoride, potassium oxide, and potassium fluoride to an appropriate amount.

[0024] (7) By adjusting the total amount of Ca oxides in terms of CaO, arc stabilization and reduction in the amount of spatter can be improved, and by adjusting the total amount of Zr oxides in terms of ZrO2, the bead shape and bead appearance can be improved.

[0025] The reasons for limiting the range of each composition in the coating of the low hydrogen iron powder covered metal arc welding electrode of the present invention will be described in detail below. The content of each component in the coating of the low hydrogen iron powder covered metal arc welding electrode is expressed in mass% relative to the total mass of the coating, and when expressing the mass%, it is simply written as %.

[0026] [Covering rate: 30-45% by mass of the total mass of the welding rod] The coverage rate of the coating material on the outer circumference of the steel core wire has a large effect on the shielding resistance during welding. If the coverage rate is less than 30% by mass of the coating material relative to the total mass of the iron powder low hydrogen type covered metal arc welding electrode (hereinafter simply referred to as %), the coating material itself becomes less, resulting in insufficient shielding, and the N content in the weld metal increases, reducing the toughness of the weld metal. On the other hand, if the coverage rate of the coating material exceeds 45%, the amount of slag increases too much and the arc becomes unstable. Therefore, the coverage rate is set to 30 to 45%.

[0027] [Mn: 3.0-6.0%] Mn is added from metal Mn, Fe-Mn, Fe-Si-Mn, etc., and is an element necessary as a deoxidizer for weld metal, and has the effect of refining the weld metal structure and increasing the low-temperature toughness and strength of the weld metal. If Mn is less than 3.0%, the strength and low-temperature toughness of the weld metal decrease. Also, if Mn is less than 3.0%, deoxidation is insufficient and blowholes are likely to occur in the weld metal. On the other hand, if Mn exceeds 6.0%, the strength of the weld metal becomes excessively high and the toughness decreases. Therefore, Mn is set to 3.0 to 6.0%.

[0028] [Ni: 3.5~7.5%] Ni is added as metallic Ni and has the effect of improving the strength and low-temperature toughness of the weld metal. If Ni is less than 3.5%, the strength and low-temperature toughness of the weld metal decrease. On the other hand, if Ni exceeds 7.5%, the strength of the weld metal becomes excessively high. Therefore, Ni is set to 3.5 to 7.5%.

[0029] [Mo: 0.3-1.3%] Mo is added in the form of metal Mo, Fe-Mo, etc., and has the effect of further improving the strength of the weld metal. If Mo is less than 0.3%, the strength of the weld metal decreases. On the other hand, if Mo exceeds 1.3%, the strength of the weld metal becomes excessively high and the toughness decreases. Therefore, Mo is set to 0.3 to 1.3%.

[0030] [Cr: 0.2~1.0%] Cr is added from metal Cr, Fe-Cr, etc., and has the effect of further improving the strength of the weld metal. If Cr is less than 0.2%, the strength of the weld metal decreases. On the other hand, if Cr exceeds 1.0%, the strength of the weld metal becomes excessively high and the toughness decreases. Therefore, Cr is set to 0.2 to 1.0%.

[0031] [Si: 2.0~5.0%] Silicon is added from metal silicon, Fe-Si, Fe-Si-Mn, etc., and is used for the purpose of deoxidizing the weld metal. If the silicon content is less than 2.0%, deoxidation is insufficient, making blowholes more likely to occur in the weld metal and making the arc unstable. On the other hand, if the silicon content exceeds 5.0%, low-melting-point oxides are precipitated at the grain boundaries of the weld metal, reducing the low-temperature toughness of the weld metal. Therefore, the silicon content is set to 2.0-5.0%.

[0032] [Total of silicon oxides converted into SiO2: 3.5-7.5%] Silicon oxide is added from silica sand, zircon sand, potassium feldspar, solid components of water glass such as sodium silicate and potassium silicate, wollastonite, etc., and has the effect of increasing the viscosity of the molten slag, ensuring slag with appropriate viscosity, and improving the bead shape. If the SiO2 equivalent value of silicon oxide is less than 3.5%, the viscosity of the molten slag will be low and the bead shape will be poor. On the other hand, if the SiO2 equivalent value of silicon oxide exceeds 7.5%, the slag will become glassy and the slag removability will be poor. Therefore, the SiO2 equivalent value of silicon oxide is set to 3.5 to 7.5%.

[0033] [Ti: 0.2~1.5%] Ti is added from metal Ti, Fe-Ti, etc., and is effective as a deoxidizer, and at the same time, has the effect of lowering the potential gradient of the arc and stabilizing the arc. In addition, it has the effect of refining the weld metal structure and improving the low-temperature toughness of the weld metal. If Ti is less than 0.2%, this effect cannot be obtained and the arc becomes unstable. Also, if Ti is less than 0.2%, the amount of oxygen in the weld metal increases and the microstructure of the weld metal is not refined, so the low-temperature toughness of the weld metal decreases. On the other hand, if Ti exceeds 1.5%, the precipitation of Ti oxide in the weld metal increases, and the low-temperature toughness of the weld metal decreases. Therefore, Ti is set to 0.2 to 1.5%.

[0034] [Total of Ti oxides converted into TiO2: 1.0~5.0%] Ti oxide is added from rutile, titanium oxide, titanium slag, calcium titanate, etc., and has the effect of stabilizing the arc and adjusting the viscosity of the molten slag to improve the bead shape. If the TiO2 equivalent value of Ti oxide is less than 1.0%, the arc becomes unstable and the bead shape becomes poor. On the other hand, if the TiO2 equivalent value of Ti oxide exceeds 5.0%, the viscosity of the molten slag becomes high and the fluidity of the slag becomes poor, resulting in a convex bead shape. Therefore, the TiO2 equivalent value of Ti oxide is set to 1.0 to 5.0%.

[0035] [Metal carbonates (single or multiple): 25~45%] Metal carbonates are added from calcium carbonate, magnesium carbonate, barium carbonate, etc., and decompose with the heat of the arc to generate CO2 gas, which has the effect of protecting the weld metal from the atmosphere. If the total of one or more metal carbonates is less than 25%, the shielding effect is insufficient and blowholes are likely to occur. If the total of one or more metal carbonates is less than 25%, nitrogen from the atmosphere is mixed into the weld metal, reducing low-temperature toughness. On the other hand, if the total of one or more metal carbonates exceeds 45%, the arc becomes unstable, the bead shape becomes convex, and slag removability is also poor. Therefore, the total of one or more metal carbonates is set to 25-45%.

[0036] [Metal fluorides (one or more): 5-15%] Metal fluorides are added from fluorite, magnesium fluoride, aluminum fluoride, lithium fluoride, sodium fluoride, potassium silicofluoride, etc., and have the effect of adjusting the fluidity of the molten slag and improving the bead appearance. If the total of one or more metal fluorides is less than 5%, the fluidity of the molten slag is poor, the slag encapsulation is poor, and the bead appearance is poor. On the other hand, if the total of one or more metal fluorides exceeds 15%, the shape of the covering tube becomes incomplete, resulting in a one-sided melting state and an unstable arc. Therefore, the total of one or more metal fluorides is set to 5-15%.

[0037] [Total of Al oxides converted to Al2O3: 2.0% or less] Aluminum oxides are added from alumina, potassium feldspar, etc., and have the effect of stabilizing the arc and improving the bead shape. However, if the total amount of aluminum oxides (Al2O3) exceeds 2.0%, the slag becomes glassy and the slag removability becomes poor. Therefore, the total amount of aluminum oxides (Al2O3) should be 2.0% or less.

[0038] [Total of Mg oxides converted to MgO: 0.8% or less] Mg oxide is added from magnesium oxide, magnesia clinker, etc., and has excellent heat resistance and is effective in suppressing the one-sided melting of the coating material. However, if the total of Mg oxide converted into MgO exceeds 0.8%, the viscosity of the molten slag increases, and the bead shape becomes convex. Therefore, the total of Mg oxide converted into MgO should be 0.8% or less.

[0039] [Total of one or more of sodium oxide, sodium fluoride, potassium oxide and potassium fluoride: 1.5% to 3.0% in terms of sodium and potassium] Na is added from Na oxides such as sodium silicate and other solid components of water glass, and Na fluorides such as sodium fluoride, and K is added from potassium silicate and other solid components of water glass, K oxides such as potassium feldspar, and K fluorides such as potassium silicate fluoride, and these have the effect of improving the paintability during the manufacture of welding rods and the stability of the arc during welding. If the total of one or more of Na oxides, Na fluorides, K oxides, and K fluorides is less than 1.5% in terms of Na and K, the arc becomes unstable. If the total of Na and K is less than 1.5%, the paintability during production is poor, and cracks are likely to occur on the coating surface during the manufacture of welding rods, reducing the productivity of the covered arc welding rod. On the other hand, if the total of Na and K exceeds 3.0%, the arc blow becomes stronger and the amount of spatter increases. Therefore, the total of one or more of sodium oxide, sodium fluoride, potassium oxide and potassium fluoride is 1.5 to 3.0% in terms of sodium and potassium. The sodium and potassium values ​​include 0%.

[0040] [Mn, Ni, Mo and Cr are 150 to 300 in formula (1)] 2.3 × [Mn] + 38.5 × [Ni] + 4.2 × [Mo] + 2.1 × [Cr] ... Formula (1) (where [ ] indicates the mass% of each component relative to the total mass of the coating material)

[0041] By optimizing the values ​​obtained by formula (1) for the above-mentioned Mn, Ni, Mo, and Cr, good bending performance of the welded joint can be obtained. If the value of formula (1) is less than 150, good bending performance of the welded joint cannot be obtained. On the other hand, if the value of formula (1) exceeds 300, the austenitic structure after welding becomes excessive, and the bending performance deteriorates. Therefore, the value of formula (1) is set to 150 to 300.

[0042] [Fe: 20-30%] Fe is added from iron powder, iron alloy powder such as Fe-Mn and Fe-Mo, or iron oxide, and has the effect of reducing the potential gradient of the arc, shortening the arc length, and preventing one-sided melting of the coating material, and is the most important raw material, especially in welding using a DC power source. If Fe is less than 20%, the arc length becomes long and one-sided melting of the coating material is likely to occur. On the other hand, if Fe exceeds 30%, the thermal conductivity becomes high, and in welding with a covered metal arc welding rod, the covered metal arc welding rod itself becomes red hot (hereinafter referred to as rod burn) in the latter half of welding, making welding difficult. Therefore, Fe is set to 20-30%.

[0043] [Total of Ca oxides converted into CaO: 0.5% or less] Ca oxide is added from calcium titanate, wollastonite, etc., and is effective in stabilizing the arc and reducing spatter generation. If the total of Ca oxide converted into CaO exceeds 0.5%, the arc becomes weak and unstable, and welding defects such as poor fusion are likely to occur. Therefore, the total of Ca oxide converted into CaO is set to 0.5%.

[0044] [Total of Zr oxides converted into ZrO2: 1.5% or less] Zirconium oxide is added from zircon sand, zirconia, etc., and has a high melting point of 2700℃, so it has stable fire resistance even when the coating material and steel core wire are overheated, and is effective in preventing the coating material from melting one-sidedly. If the total of Zr oxide converted into ZrO2 exceeds 1.5%, the viscosity of the molten slag increases, the fluidity of the slag decreases, and the bead shape becomes convex. Therefore, the total of Zr oxide converted into ZrO2 should be 1.5% or less.

[0045] The balance of the coating material of the iron powder low hydrogen type covered metal arc welding electrode of the present invention is impurities contained in the coating material and the alloy powder. Hectorite, mica, etc. are used as the coating material. Impurities contained in the alloy powder include P, S, Cu, Nb, V, B, etc. In particular, P and S both generate compounds with low melting points and reduce the toughness of the weld metal, so the total amount of impurities is adjusted to 1.0% or less.

[0046] The steel core wire used is preferably JIS G3523:1980 SWY11, but does not have to be SWY11. The C content of the steel core wire is preferably 0.08% or less, and the C content can be appropriately adjusted from the coating material to adjust the strength. P in the steel core wire reduces toughness, so it is preferable that it is 0.010% or less, and S reduces the fluidity of the slag, so it is preferable that it is 0.010% or less. EXAMPLES

[0047] The effects of the present invention will now be described in more detail with reference to examples.

[0048] A JIS G3523:1980 SWY11 steel core wire (C: 0.08%, Si: 0.02%, Mn: 0.46%, P: 0.009%, S: 0.006%) with a diameter of 4.0 mm and length of 400 mm was coated with a coating agent having the composition shown in Table 1 at the coverage shown in Tables 1 and 2, and then dried to produce various iron powder low hydrogen covered metal arc welding electrodes. K0116 The ICP emission spectrometry method described in :2014 was used for the investigation. The coating of the prototype welding rod was peeled off, and the sample was collected and crushed into a powder sample. The powder sample was decomposed using the acid decomposition method or the alkali fusion method. A part of the solution was sprayed and introduced into the argon plasma of the ICP emission spectrometry analyzer, and the emission intensity of the analytical line of the quantitative component or the ratio of the emission intensity of the analytical line of the quantitative component to the emission intensity of the internal standard element was measured. The concentration of the measurement target element in the sample solution was determined from the obtained emission intensity using the calibration curve method. In addition, X-ray diffraction analysis was used for the quantitative analysis of metals and oxides such as Si and SiO2. For example, the amount of Si in the coating was specified using the ICP emission spectrometry method, and the metal Si and oxide Si were measured using the same coating by the X-ray diffraction analysis method, and the quantitative analysis values ​​for each were obtained. In order to improve the analytical accuracy, it is desirable to crush the coating into fine particles of 10 μm or less using an agate mortar or the like. The procedure for filling the sample was as follows: a glass sample plate was placed on a flat glass plate measuring 10 cm square and approximately 5 mm thick, and the glass plate was used to hold the plate in a groove approximately 0.5 mm deep. The surface of the sample plate and the sample surface were finished to be flush with each other, and the sample was then analyzed using an X-ray diffraction analyzer.

[0049] [Table 1]

[0050] [Table 2]

[0051] Using the above-mentioned various prototype welding rods, weld metal specimens were prepared by forming a backing groove with a groove angle of 20° and a root gap of 16 mm on a 20 mm thick steel plate with the composition shown in Table 3, and welding current: 170 A, welding heat input: 19 kJ / cm, preheating and interpass temperature: 95 to 120°C using a DC power source. Furthermore, a butt V-groove with a groove angle of 60°C, root face: 2 mm, and root gap: 2.5 mm was formed on a 20 mm thick steel plate with the composition shown in Table 3, and welding and back chipping were performed using a DC power source, and welding was performed under the same conditions to prepare welded joints.

[0052] [Table 3]

[0053] [Table 4]

[0054] The welding workability was evaluated by visually inspecting the arc stability, amount of spatter, bead shape, bead appearance, slag detachability, one-sided melting, and rod burn during the above welding using each prototype welding rod. After welding, an X-ray transmission test was performed according to AWS A5.5 to check for the presence of welding defects. Tensile test pieces (AWS B4.0:2007) and V-notch impact test pieces (AWS B4.0:2007) were taken from the center of the plate thickness of the weld metal test pieces. In the tensile test, a tensile strength of 810 to 920 MPa was considered good. For the evaluation of toughness, a Charpy impact test was performed at a test temperature of -50°C, and the average of the absorbed energy of 3 times, excluding the minimum and maximum values, of 5 times was considered good if it was 40 J or more. For the evaluation of bending performance, bending test pieces (AWS B4.0:2007) were taken from the welded joints. A total crack length of 3.2 mm or less was considered to be pass, and a total crack length of more than 3.2 mm was considered to be fail. The test results are summarized in Table 5.

[0055] [Welding workability] (Arc Stability) If the arc was stable during welding and did not disappear, it was rated as good, and if the arc disappeared even once, it was rated as poor.

[0056] (Amount of spatter generated) It is preferable that the amount of spatter generated during welding is small. Specifically, a copper collection box was used to measure the weight of spatter generated during 1 minute of welding to determine the value per unit time (g / min). The spatter was measured five times under the welding conditions shown in Table 4, and the average value was calculated. A value of 2.0 g / min or less was considered good.

[0057] (Bead shape / bead appearance) It is preferable that the bead waveform of the deposited metal is uniform and free of disturbance, and that there is no undercut or overlap that requires rework. It is preferable that the deposited metal has a bead shape with excellent uniformity in the excess height and bead width. Specifically, a case where the bead waveform of the deposited metal is disturbed or where undercut or overlap that requires rework occurs on the bead surface of the deposited metal is determined as defective.

[0058] (Slag removability) It is preferable that the solidified slag on the weld bead surface can be easily removed after welding. After welding, the solidified slag on the weld bead surface was struck with a chipping hammer (total length 300 mm, weight 350 g) by swinging it down lightly in an arc around the handle. If the slag cracked and could then be easily removed, it was rated as good, and if the slag did not crack, it was rated as poor.

[0059] (Partial dissolution of coating material) It is preferable that the arc is generated parallel to the welding rod without any chipping of the coating material during welding, and that the arc spread is uniform and stable. If part of the coating material is chipped during welding, the arc is deflected in a direction other than parallel to the welding rod, and the arc spread is non-uniform, it is rated as defective.

[0060] (stick burn) It is preferable that the coating does not fall off during welding because the welding rod becomes red hot. A welding rod that does not change color during welding is rated as good, and a welding rod that becomes red hot and turns red is rated as bad.

[0061] [Welding defects] Specifically, X-ray examination was performed in accordance with AWS A5.5 to judge the presence or absence of defects in the weld metal. A specimen without any defects was rated as good, and a specimen with even one defect was rated as poor.

[0062] [Table 5]

[0063] Welding rods No. 1 to No. 13 in Tables 1, 2 and 5 are examples of the present invention, and welding rods No. 14 to No. 28 are comparative examples. In the present invention, No. 1 to No. 13 are suitable in terms of the coating material Mn, Ni, Mo, Cr, Si, Si oxide in terms of SiO2, Ti, Ti oxide in terms of TiO2, metal carbonate, metal fluoride, total of Al oxide in terms of Al2O3, total of Mg oxide in terms of MgO, Na oxide, Na fluoride, total of Na and K values ​​of one or more of K oxide and K fluoride, Fe, and coverage. Therefore, the arc condition was good, the amount of spatter generation was small, the condition of the protective tube was good, no rod burn occurred, and the welding workability was good, such as good bead appearance, bead shape, slag removability and slag encapsulation, good productivity, no welding defects, and good tensile strength and absorbed energy of the weld metal. Since the value of the following formula (1) was appropriate, the bending performance of the weld metal was also good, and the results were very satisfactory.

[0064] 2.3 × [Mn] + 38.5 × [Ni] + 4.2 × [Mo] + 2.1 × [Cr] formula (1) Here, [ ] indicates the mass % of each component relative to the total mass of the coating agent.

[0065] Furthermore, since Nos. 6, 10, and 11 had an appropriate total amount of Ca oxide converted into CaO, the arc condition was better than the other inventive examples, and there was less spatter.

[0066] In addition, since the total amount of Zr oxide converted into ZrO2 was appropriate in Nos. 1, 3, and 12, the one-sided dissolution of the coating material was suppressed more than in the other inventive examples.

[0067] Among the comparative examples, welding rod No. 14 had a large amount of Mn and a small amount of Si, and therefore the tensile strength of the deposited metal was high, the absorbed energy was low, the arc was unstable, and blowholes were generated.

[0068] Welding rod No. 15 had a high coverage rate, low Mn content, and low SiO2 equivalent value of silicon oxide, so the deposited metal had low tensile strength, low absorbed energy, poor bead shape, unstable arc, and blowholes.

[0069] Welding rod No. 16 had a high Ni content, a high total Al2O3 equivalent value, and a high total Na equivalent value and K equivalent value, so the tensile strength of the weld metal was high, the slag removability was poor, the arc was strong, and there was a lot of spatter. Furthermore, because the value of the following formula (1) was high, the weld metal failed the bending test.

[0070] 2.3 × [Mn] + 38.5 × [Ni] + 4.2 × [Mo] + 2.1 × [Cr] formula (1) Here, [ ] indicates the mass % of each component relative to the total mass of the coating agent.

[0071] Welding rod No. 17 had a low Ni content and a high total metal carbonate content, so the tensile strength and absorbed energy of the weld metal were low, the slag removability was poor, the bead shape was convex, and the arc was unstable. Furthermore, because the value of the following formula (1) was small, the weld metal failed the bending test.

[0072] 2.3 × [Mn] + 38.5 × [Ni] + 4.2 × [Mo] + 2.1 × [Cr] formula (1) Here, [ ] indicates the mass % of each component relative to the total mass of the coating agent.

[0073] Welding rod No. 18 contained a large amount of Mo and a large amount of metal fluorides in total, so the tensile strength of the weld metal was high, the absorbed energy was low, the arc was unstable, and one-sided melting occurred.

[0074] Welding rod No. 19 had a small amount of Mo and a small amount of total metal fluorides, so the tensile strength of the weld metal was low, the slag encapsulation was poor, and the bead appearance was poor.

[0075] Welding rod No. 20 had a high Cr content and a low TiO2 equivalent value, so the tensile strength of the weld metal was high, the absorbed energy was low, the bead shape was poor, and the arc was unstable.

[0076] Welding rod No. 21 had a low Cr content and a low total of Na and K values, so the tensile strength of the weld metal was low, the arc was unstable, and productivity was poor.

[0077] Welding rod No. 22 contains a lot of Si and Fe, so the absorbed energy is low and rod burn occurred.

[0078] Welding rod No. 23 had a low Ti content, a high TiO2 equivalent value of Ti oxide, and a low Fe content, so the absorbed energy was low, the bead shape was convex, the arc was unstable, and one-sided melting occurred.

[0079] Welding rod No. 24 had a high SiO2 equivalent value of Si oxide and a high Ti content, so the absorbed energy was low and the slag removability was poor. Furthermore, Ca oxide was added, but the total CaO equivalent value of Ca oxide was high, so the arc was unstable and poor fusion occurred.

[0080] Welding rod No. 25 had a low total amount of metal carbonate, so the absorbed energy was low and blowholes occurred. Furthermore, Zr oxide was added, but the total amount of Zr oxide converted to ZrO2 was high, so the bead shape was convex.

[0081] Welding electrode No. 26 had a low coverage and a high total MgO equivalent value of MgO oxide, so the absorbed energy was low and the bead shape was convex.

Claims

1. In an iron powder low hydrogen type covered metal arc welding electrode for multi-layer welding using a DC power source for 780 MPa class high tensile steel, the steel core wire is coated with a coating material, The coverage of the coating material is 30 to 45% by mass relative to the total mass of the welding rod; The composition of the coating agent is expressed as a mass % based on the total mass of the coating agent, Mn: 3.0 to 6.0%, Ni: 3.5-7.5%, Mo: 0.3 to 1.3%, Cr: 0.2-1.0%, Si: 2.0 to 5.0%, Silicon oxide SiO 2 Total conversion value: 3.5-7.5%, Ti: 0.2 to 1.5%, Ti oxide TiO 2 Total conversion value: 1.0-5.0%, Total of one or more metal carbonates: 25-45%; One or more metal fluorides in total: 5 to 15% Al oxide Al 2 O 3 Total conversion value: 2.0% or less, The total amount of magnesium oxides converted into MgO is 0.8% or less. One or more of Na oxide, Na fluoride, K oxide, and K fluoride in total: 1.5 to 3.0% in terms of Na and K, and the Mn, Ni, Mo and Cr are 150 to 300 in formula (1); Further, Fe: 20 to 30% is contained, 1. An iron powder low hydrogen type covered metal arc welding electrode, characterized in that it is coated with a coating material having a total impurity balance of 1.0% or less. 2.3 × [Mn] + 38.5 × [Ni] + 4.2 × [Mo] + 2.1 × [Cr] ... formula (1) Here, [ ] indicates the mass % of each component relative to the total mass of the coating agent.

2. The coating agent is, in mass % based on the total mass of the coating agent, Total Ca oxide converted to CaO: 0.5% or less 2. The low hydrogen iron powder covered metal arc welding electrode according to claim 1,

3. The coating agent is, in mass % based on the total mass of the coating agent, Zr oxide ZrO 2 Total conversion value: 1.5% or less 3. The low hydrogen iron powder covered metal arc welding electrode according to claim 1,

Citation Information

Patent Citations

  • Low-hydrogen coated electrode

    JP2010110817A

  • Low hydrogen based covered electrode

    JP2010227968A

  • Low-hydrogen type coated electrode

    JP2010253495A

  • Low hydrogen type covered electrode

    JP2014151338A

  • Low hydrogen type covered electrode

    JP2014188540A